Orientation towards life among a sample of students from the Faculty of Law at Sebha University in light of some variables. (Sebha University Conference Proceedings, 2024)
The aim of the current research is to identify the extent to which the students of the Faculty of Law at Sebha University have an orientation towards life, and to reveal statistically significant differences in the orientation towards life in Sebha according to the variables of gender and academic year. To achieve these objectives, the life orientation scale prepared by the researchers was used. After ensuring the validity and reliability of the scale, it was applied to a stratified random sample estimated at (68) male and female students from the Faculty of Law at Sebha University, whose number was estimated at (18) students, and (50) with a representation rate of (25%) of community members, using the descriptive analytical approach. The results of the research reached: The level of orientation towards life among a sample of students from the Faculty of Law at Sebha University exceeds the hypothesized mean. There are no statistically significant differences in orientation towards life among a sample of students from the Faculty of Law at Sebha University in light of some variables attributed to the gender variable. There are no significant differences. Statistical significance in the orientation towards life is attributed to the variable of the academic year as a whole, while there are statistically significant differences in the orientation towards life among a sample of students from the Faculty of Law at Sebha University in light of some variables attributed to the variable of the academic year and in favor of second-year students.